School – the space of book culture. Bibliological research - Socha, Irena (Interdyscyplinarium nauk o mediach i kulturze, 2020)
In the study about the book in various historical and cultural contexts, the school’s “bibliological objects” were examined, among them, the library and other book collections for the needs of the didactic process; programs and didactic realizations intended to teach reading and learning to read; various certificates of pupils’ and teachers’ reading, both community and individual. The main concepts and directions of research were defined in reference to representative examples of research in the field of Polish historical and applied bibliology from the last thirty years, regarding the culture of the school book from the Middle Ages to the end of the 50s. At the same time, “tangential fields” of bibliological research in this subject were presented with studies in the humanities and social sciences, especially in the history of education and upbringing. Attention was paid to those categories used in the theory of bibliology that are useful and even necessary for historical and cultural research. The collected examples convince us that the perspective of observation clearly shifted, not only in the science about the book, from “classic” objects, such as libraries, book collections, book institutions and editorial copies, into repertoires – canons of reading, in order to read their cultural meanings and function. The resources of the school book were examined not only because of formal features – editorial and writing, but above all as sui generis cultural projects – transferring a specific model of knowledge and competence and a system of values.